Correlational Descriptive Analysis of Digital Literacy Among Generation Z Prospective Teachers - Asyti Febliza; Putri Ade Rahma Yulis; Zul Afdal (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the level of digital technology literacy among Generation Z pre-service teachers and to examine its relationship with gender and age. The research employed a quantitative approach with a descriptive correlational design. A total of 722 students from four majors, namely science, social sciences, languages, and arts, aged 18 to 23 years, participated in this study. The instrument used was a digital technology literacy questionnaire consisting of 33 items on a four-point scale. The questionnaire covered five main indicators: personal computer, smartphone, social media, online safety, and e-learning. The instrument passed validity and reliability testing with a Cronbach’s Alpha value of 0.684, indicating acceptable internal consistency.The findings show that the digital literacy level of Generation Z pre-service teachers is in the high category, with an average score of 79 percent. The smartphone, online safety, and personal computer indicators achieved the highest scores, while the social media and e-learning indicators were in the moderate category. Analysis by major also revealed consistently high levels of digital literacy, with scores between 79 and 80 percent. The chi-square test indicated a significant relationship between gender and digital literacy, while no significant relationship was found between age and digital literacy.These results indicate that Generation Z pre-service teachers have strong readiness in using digital technologies but still require strengthening in social media and e-learning literacy. The study provides important implications for educational institutions in designing curricula and learning strategies that support the development of digital competence in future teachers.